Mediation role of cardiorespiratory fitness on association of physical activity and physical literacy among 8–12 years old children: the PAK-IPPL cross-sectional study - Hadier, Syed Ghufran; Yinghai, Liu; Long, Liu; Hamdani, Syed Danish; Hamdani, Syed Muhammad Zeeshan Haider (Frontiers in Pediatrics, 2024)
Background The effect of cardiorespiratory fitness (CRF) on the relationship of physical activity (PA), and physical literacy (PL) in 8–12 Pakistani children are largely unknown. Therefore, this study aims to examine the mediating role of CRF in the relationship between PA and PL in this demographic. Methods This cross-sectional study involved 1,360 children aged 8–12 (mean age = 10.00, SD = 1.41 years) from 85 higher secondary schools in South Punjab, Pakistan. Data were collected during the 2020–2021 academic year using the Canadian Assessment of Physical Literacy-2 (CAPL-2) protocol to assess physical activity (PA), Body Mass Index (BMI), and PL levels. CRF was measured using the PACER (Progressive Aerobic Cardiovascular Endurance Run) test. Descriptive statistics, independent samples t-tests, Chi-squared tests, and Generalized Additive Models for Location, Scale, and Shape (GAMLSS) were used for age and sex-specific CAPL-2 scoring. Associations among components were evaluated through Pearson's correlation, multivariate logistic regression, and mediation analyses. Results The study revealed that boys had significantly higher scores in CRF, PA, and PL across all age groups compared to girls (p < 0.001), with boys' scores being 20%, 10%, and 14% higher, respectively, than those of girls. Conversely, overweight children showed significantly reduced PA and PL levels (p < 0.001). An inverse correlation was found between BMI and CRF (r2 linear = 0.022; quadratic = 0.028). CRF scores had significant negative correlations BMI (r = −0.143) and positive associations with MVPA, PA, DB, and PL (r ranging from 0.241 to 0.624). CRF was observed to partially mediate the association between MVPA and PL. The direct impact of PA on PL was significant and meaningful (β = 0.002, p < .001). Additionally, the indirect effect of PA on PL through CRF was also significant (β = 0.001, p < .001), indicating that CRF serves as an important mediator in this relationship. The combined total effect of PA on PL, which includes both direct and mediated pathways, was robust and highly significant (β = 0.003, p < .001). Conclusion The study revealed a strong positive correlation between CRF, PA, and PL, but a negative one with BMI in South Punjab children aged 8–12. Notably, CRF and PA emerged as significant predictors of PL levels in this population. Consequently, interventions that are both systematic and targeted towards improving these factors should be implemented as strategies to enhance children's PL levels and promote physically active behaviors.